PENGARUH PENGGUNAAN NAUNGAN TERHADAP PERTUMBUHAN DAN HASIL DUA VARIETAS TANAMAN KACANG MERAH ( Phaseolus vulgaris L. ) - Ai Komariah; Erwin Christian Waloeyo; Odang Hidayat (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2017)
The research aims to obtain varieties of red beans was tolerant oflow light intensity under this shade.The research implemented in the experimental garden UNWIM BojongSeungit campus, from late June to early September 2016, with a height of 850 meters above sea level and precipitation type C (Dampish ).The experimental design used was split plot design consisting of 16 treatments and 4 Deuteronomy .Treatment consists of two levels : size of the shade (P), p0 = 0%Shade, p1 = 50% Shade, p2 = 65% Shade, p3 = 75%Shade, and varieties (v), v1 = Garut and v2 = Tasik.The results of this experiment showed the effect of growth and different results in higher plants in shade 65% and 0% in the varieties of Garut and Tasik age 35 days after planting, number of leaves per plant and the number of branches per plant at 28 days after planting in the shade of 75%, the number of pods contents per plant and the number of pods per plant in the shade of 0% whereas 50% shade highest yield of dry grain weight per plant, weight of 100 grains of seed varieties Garut and percentage (%) number of pods per plant were highest in varieties Tasik Varieties of Garut and Tasik are sensitive to shade 75%, moderate to 65% shade and still tolerant to shade 50%.